The Role of Images as Models in Biology Teaching and Learning: Enhancing Conceptual Understanding in Secondary Schools in Delta State, Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
The study examined the role of images as models in enhancing conceptual understanding of biology among secondary school students in Delta State, Nigeria. Biology education often involves abstract concepts that are difficult for students to comprehend through text-based instruction alone. This quasi-experimental study adopted a non-equivalent pre-test, post-test control group design to investigate the effectiveness of integrating images-as-models strategies into biology teaching. A total of 360 senior secondary students from six public schools were sampled, with 180 students in the experimental group and 180 in the control group. Data were collected using a Biology Achievement Test (BAT) and a questionnaire on visual aid usage administered to 12 biology teachers. Descriptive statistics summarized teachers’ perceptions of visual aid availability and challenges, while inferential statistics, including ANCOVA and paired-sample t-tests, assessed differences in student performance and knowledge retention. Results indicated that the experimental group achieved significantly higher post-test scores compared to the control group, demonstrating the effectiveness of images as models in enhancing conceptual understanding. Furthermore, delayed post-test results revealed better retention among students exposed to visual aids. Teachers reported limited availability of projectors, videos, and models, as well as insufficient training, as key barriers to effective implementation. The study concludes that integrating images-as-models strategies in biology instruction significantly improves students’ learning outcomes and retention. Recommendations include provision of multimedia resources, targeted teacher training, curriculum enhancement, and infrastructure improvements to support the use of visual aids.